Effectiveness of Rental Apartment Management in Mariso Sub-District, Makassar City - Halim, Didin; Guntur, Muhammad; Putri, Nur Dzakiyah Dwi; Rukmana, Novayanti Sopia (Jurnal Aktor, 2024)
This research includes descriptive qualitative research with data collection techniques through observation, interviews, and documentation. Data analysis techniques consist of data collection, data condensation, data presentation and conclusions. The results showed that the Effectiveness of Rental Flats Management carried out by the Rusunawa Regional Technical Implementation Unit has not been effective. The management of Rental Flats in Mariso District, Makassar City has not been effective in terms of the dimensions of goal achievement, integration, adaptation and can be seen from the aspects of planning, organizing, implementing and supervising. In the aspect of planning the management of Rusunawa, good management effectiveness is needed so that the objectives of Rusunawa Development are in accordance with the designation of development. Related to the aspect of organizing still requires awareness from the manager regarding their respective duties and functions. The implementation aspect still requires coordination between the management of Rusunawa and residents of Rusunawa related to handling problems and complaints of each occupant unit. The supervision aspect of Rusunawa requires improved management related to security conditions, improving the physical condition of buildings and physical conditions of the environment, so that the purpose of Rusunawa Development is in accordance with the designation of its development.